As novas vias da ontologia em György Lukács : as bases ontológicas do conhecimento - Ronaldo Vielmi Fortes (2011)
The thesis analyzes the late works on the theme of the Ontology of Social Being, written by György Lukács in the period between 1963 to 1970. Seeks to identify the elements of the work Marxist, according to the author, set up a profound inflection with the previous philosophical thought, devoting himself especially to the problem of the ontological foundations of knowledge.